Lifetime-weighted photoacoustic imaging. (7th November 2016) - Forbrich, A; Shao, P; Shi, W; Zemp, Roger J
Abstract: Photoacoustic (PA) imaging has been utilized to quantify the lifetime profile of exogenous agents using a series of pump-probe pulses with a varying time delay; however, current techniques typically lead to long acquisition times which are sensitive to motion and cause absorption or photobleaching. We introduce a technique called lifetime-weighted imaging, which uses only three laser pulses to preferentially weight signals from chromophores with long lifetimes (including exogenous contrast agents with triplet excited states such as methylene blue and porphyrins) while nulling chromophores with short picosecond- to nanosecond-scale lifetimes (including hemoglobin). This technique detects the PA signal from a probe pulse either with or without a pump pulse. By subtracting the probe-only signal from the pump-present probe signal, we effectively eliminate signals from chromophores with short lifetimes while preserving PA signals from chromophores with long-lifetimes. We demonstrate the oxygen-dependent lifetime of both methylene blue and porphyrin-lipids and demonstrate both ground-state recovery and excited-state lifetime-weighted imaging. Lifetime-weighted PA imaging may have applications in many molecular imaging application including: photodynamic therapy dosimetry guidance and oxygen sensing.